Macaronics as What Eludes Translation. - Saussy, Haun (Paragraph, 2015)
'Translation' is one of our all-purpose metaphors for almost any kind of mediation or connection: we ask of a principle how it 'translates' into practice, we announce initiatives to 'translate' the genome into predictions, and so forth. But the metaphor of translation - of the discovery of equivalents and their mutual substitution - so attracts our attention that we forget the other kinds of inter-linguistic contact, such as transcription, mimicry, borrowing or calque. In a curious echo of the macaronic writings of the era of the dawn of print, the twentieth century's avant-garde, already foreseeing the end of print culture, experimented with hybrid languages. Their untranslatability under the usual definitions of 'translation' suggests a revival of this avant-garde practice, as the mainstream aesthetic of the moment invests in 'convergence' and the subsumption of all media into digital code.